Intellectual disability stigma and initiatives to challenge it and promote inclusion around the globe. Issue 2 (6th January 2020) - Scior, Katrina; Hamid, Aseel; Hastings, Richard; Werner, Shirli; Belton, Catherine; Laniyan, Adebisi; Patel, Maya; Kett, Maria
Abstract : There is a dearth of studies that have examined the attitudes of society toward people with intellectual disabilities (IDs) on a global scale. This study set out to gauge the extent to which ID continues to be stigmatized and to which initiatives are in place to increase their inclusion and tackle stigma around the globe. Data were collected using a web survey from 667 experts and organizations in the (intellectual) disability field pertaining to 88 countries and covering all world regions. Information about the study was disseminated by four multinational disability organizations, and the survey was available in five languages. Findings and responses indicated that the general public in many parts of the world broadly support the fundamental principle of inclusion of children and adults with IDs, yet negative attitudes persist. High levels of stigma and denial of fundamental rights still appeared a reality in many places. Initiatives to tackle stigma appeared patchy and least in evidence where they were most needed. In many parts of the world the life chances of people with IDs often appear still very poor, and support and advocacy almost entirely their families' responsibility. More needs to be done globally to reduce the stigma associated with ID and to promote active engagement and regular social interactions between persons with IDs and their fellow citizens without IDs.